Trip Generation Model for Gboko Town, Benue State, Nigeria - Mchi, Akaawase Alexander; Umoren, Victor (Journal of Sustainability and Environmental Management, 2023)
Nowadays many urban planning authorities especially in less developed countries have been struggling with traffic related challenges like traffic congestion, air pollution and traffic accidents in their cities. However, solutions to these problems cannot be achieved without rational planning decisions and cannot be attained without the basic understanding of the urban transport system. This study was carried out to assess commuter trip generation in Gboko town, Benue State with a view to estimate long-range future travel demand that would accommodate future transportation needs. Trip generation data was collected from 440 households using questionnaire and travel diary. The information from questionnaire and travel diary was used to prepare the origin-destination matrix, and gravity model was used to translate trip distribution into trip length frequency. Work trip had the greatest trip percentage (%) share among other trip purposes and was proxy for trip distribution. The 25-minute work trips dominated the urban trip pattern in Gboko town with 17.01 % annual increase. It implied that people would take much longer time and distance to reach their destination in Gboko town due to the large expanse of the town, or due to deficiency in public transit facilities and poor road infrastructure. Trip generation and distribution models for Gboko town provided accurate scenarios of the current travel pattern in the town and aided in forecasting future travel situations in the study area. The study recommended that urban transportation policy should encourage provision of public transit buses, incentives for public transit users and improve on the road network system to shorten the trip length frequency of the town.